MODEL DAN PRAKTIK: ASESMEN FORMATIF NON PAPER-BASED DALAM PEMBELAJARAN BAHASA ARAB - Wanti, Adella Ira; A'yuni, Qurrotul; Chamidah, Dewi (Arabi : Journal of Arabic Studies, 2022)
This article aimed to develop designs for non-paper-based (NPB) formative assessment models in Arabic learning accompanied by assessment instruments, practices, and student perspectives at the elementary school level. The method used is a qualitative field study with eight participants selected purposively. After teaching for two months, data were collected through observation, documentation, and interviews”data analysis using Miles and Huberman's theory, namely reduction, presentation, and drawing reports. The results of the study show that teachers have designed and implemented NPB formative assessments: Jawab kuIS!, Ù…ÙŽÙ†Ù’ Ø£ÙŽØ³Ù’Ø±ÙŽØ¹Ù’ ÙŠÙŽØ±Ù’Ø¬ÙØ¹Ù’, KEPO nih!, dan Klik Klik Quizizz which utilizes Instagram, Canva, and Quizizz applications. The student's perspective on this practice is positive, evidenced by students preferring NPB formative assessments to conventional paper-based formative assessments cause for them the assessment is exciting, tend to be enthusiastic about participating in the assessment, and expect formative and summative assessments in the future always to use the NPB model.